Recurrent bleb infections. Issue 8 (1st August 1998) - Waheed, Samra; Liebmann, Jeffrey M; Greenfield, David S; Ritterband, David C; Seedor, John A; Shah, Mahendra; Ritch, Robert
Abstract : AIM: To report the patient characteristics, causative organisms, and clinical outcomes in patients with recurrent bleb related ocular infections. METHODS: The medical records of all patients diagnosed with bleb related ocular infection at the New York Eye and Ear Infirmary over a 10 year period were reviewed. Recurrent bleb infection was defined as at least two episodes of bleb purulence with or without associated intraocular inflammation separated by a quiescent period of at least 3 months. RESULTS: Recurrent bleb infections developed in 12 eyes of 12 patients (10 men, two women) a mean of 16.3 (SD 17.9) months (range 3–51 months) after the initial infection. Two patients developed a third episode 3 and 20 months, respectively, after the second infection, yielding a total of 14 recurrent infection episodes. Recurrent infection developed after trabeculectomy in 11 eyes (adjunctive 5-fluorouracil, nine eyes; mitomycin C, one eye; no antifibrosis agent, one eye) and following cataract extraction with inadvertent bleb formation in one eye. Four (36.4%) of the filtered eyes had undergone trabeculectomy at the inferior limbus. The mean follow up time from filtering surgery to the first bleb related infection was 28 months for the nine patients treated with 5-fluorouracil and 14 months for the single patient treated with mitomycin C. 11 (78.6%) cases had a documented bleb leak in the 4 week period before or at the time of recurrent infection. Topical, prophylactic antibiotics had been used in 7/14 (50%) cases. The same organism was cultured from the initial and recurrent infections in 2/14 (14.3%) cases. CONCLUSION: Eyes that have been successfully treated for bleb related infection remain at risk for recurrent infection. No apparent correlation exists between organisms responsible for the initial and recurrent infections. The increased rate of recurrent bleb related infection in patients receiving adjunctive 5-fluorouracil compared to mitomycin C may have been related to the longer follow up of the 5-fluorouracil eyes.